Equity in our education system - Doyle, Jennifer (My University, 1992)
This paper focuses on the quest for equity in the education system of Trinidad and Tobago. It also provides an overview of the concept of equity, and discusses equity issues in education.
Biennial Cross-Campus Conference on Education, 2nd, St. Augustine, Trinidad, 22-24 April, 1992
Keywords: equal education